Rivest Shamir Adleman (RSA) Super Encryption Algorithm with Vigenere Cipher Algorithm Modification for Image Security - Mariza; , Achmad Fauzi; Yani Maulita (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
The development of information technology makes information easy to transfer and transmit digital media such as images and videos, but also brings security risks to data that is vulnerable to being infiltrated by irresponsible parties. Digital image security is a major concern in areas such as design security, medical science and architecture. Cryptography is a solution for protecting digital images, where encryption and decryption are the core. This research proposes a double encryption algorithm that combines Rivest Shamir Adleman (RSA) and Vigenere Cipher. The RSA algorithm, as the leading asymmetric cryptography algorithm, is used to secure the Vigenere key, which is then used to encrypt the image. This approach provides multiple layers of security, making attacks on images more difficult. The aim of this research is to analyze and implement the RSA algorithm with the Vigenere Cipher modification in digital image encryption, as well as evaluating the effectiveness, security and efficiency of the algorithm. The results show the success of this approach in protecting digital images from data attacks and hacking, although there is still room for improvement. In addition, this algorithm provides security without sacrificing the quality of the digital image. This research contributes to the development of digital image security methods, which are important in today's information age. By using this dual encryption approach, this research provides a solution that can be applied in a variety of contexts, maintaining the security and integrity of digital data in the face of increasingly complex threats.